Benign monomelic amyotrophy of lower limb in a cohort of chinese patients. Issue 4 (2nd March 2021) - Wang, Lulu; Wen, Han; Chen, Shuyun; Wang, Huan; Zheng, Yilei; Chen, Ran; Li, Jingjing; Jiang, Kaiyan; Xiang, Haijie; Zhu, Min; Zhou, Meihong; Yao, Sheng; et al.
Abstract: Background: Benign monomelic amyotrophy of lower limb (BMALL) is a neurogenic syndrome representing an unclear field. Further studies might be helpful to elucidate uncertainties regarding causation, outcome, and the risk of progression to amyotrophic lateral sclerosis (ALS). Methods: According to the inclusion and exclusion criteria, 37 patients with BMALL were retrospectively collected in three neuromuscular centers from January 2012 to October 2018. The detailed medical data were summarized. Multiple laboratory tests were examined. Routine electrophysiological examinations, muscle MRI of lower limbs, and muscle biopsy were conducted. Results: The cohort included 24 male and 13 female cases with median age of onset 47 years. Muscle MRI revealed that the distribution of involved muscles matched with the extent of fat infiltration, so the pattern muscle atrophy can be divided into the following four types: six patients with thigh atrophy (type I), 14 patients with leg atrophy (type II); 10 patients with disproportionate atrophy in both thigh and leg (type III); and seven patients with well‐proportionate atrophy in both thigh and leg (type IV). Electrophysiological findings showed neurogenic pattern, spontaneous activity, and abnormal H reflex, which suggested a disorder of spinal anterior horn cell in the patients with types I‐III. However, no electrophysiological abnormalities were found in the patients with type IV. Muscle pathology varied from almost normal pattern to advanced neurogenic pattern in nine biopsied patients. Follow‐up showed that two patients with type II developed to ALS four years later, and all patients with type IV were in stable condition without any complaints. Conclusion: Muscle MRI was useful to exactly localize the distribution of involved muscles in BMALL patients. The distribution of atrophic muscles can be roughly divided into four types based on the MRI features. The classification of distributing types might be as an indicator for the prognosis of BMALL. Abstract : Benign monomelic amyotrophy of lower limb (BMALL) is a neurogenic syndrome representing an unclear field. This study might be helpful to elucidate uncertainties regarding causation, outcome, and the risk of progression to amyotrophic lateral sclerosis (ALS).